Assessment of Potential, Opportunities, Challenges, and Gaps of Fodder for Sustainable Livestock Production in Bardhere District, Somalia. - Hassan, Abdihamid Salad; Barre, Abdirahman; Mohamed, Abdullahi Nur; Mohmed, Shafii Abdullahi; Farah, Abdirizak Nor; Ahmed, Mahad Aden; Ahmed, Abdishakuur Ali (Multidisciplinary Journal of Horseed International University (MJHIU), 2024)
Fodder refers particularly to feed of a vegetative nature given to the animals (including plants cut and carried to them), for Sustainable farm animal raising of sufficient quantities and quality of forages and fodder, rather than that which they forage for themselves. It includes hay, straw and silage. Therefore, the purpose of this review paper was to explore the potential, opportunities, challenges and gaps in fodder production in arid and semiarid regions at the Bardhere district of Gedo, Somalia. For describing the evaluation of potential, opportunities, challenges and gaps in fodder production, descriptive survey designs were used. The information was gathered between November 2022 and June 2023. A questionnaire was used to collect data. The total number of respondents was 80 across various fields (livestock farmers and forage producers in bardhere district). The data was arranged and analysed by using SPSS. The researchers met all of their study objectives and came up with a beneficial: The researchers met all of their study objectives and came up with a beneficial conclusion. The majority of the respondent 65% answer 18 and 45 between ages. The majority of the respondents (81.25%) were male, while only 18.75% percent were female, according to the study. The researcher discovered that 63.75% percent of the respondents were married, while 6.25% were widow and divorced. However, 18.75% of the respondents were single, and 11.25% were just window. According to the educational background, 33.75%were illiterates, 30% were primary school, 30%had secondary education and 16.25% had of university. The bulk of the respondents were farmers, with 57.75%being farmers, 21.25 percent being livestock keepers, 11.25% being fodder traders and 10% prevented then others specific tread according to the study. The majority of respondents main challenge of fodder production answered 50.5% disagree. Therefore, it is strongly suggested that forage should be promoted into the sustainable livestock production and the environment, particularly in the country’s arid and semiarid regions.